Body appearance values modulate risk aversion in eating restriction - Jenkinson, Paul Mark (J Exp Psychol Gen, 2023)
The understanding of eating disorders is hindered by the lack of integration between existing psychosocial and neurobiological approaches. We address this problem by developing a novel transdiagnostic and computational approach to eating restriction decisions. We first validated a novel paradigm which extends an established monetary risk task to involve body stimuli with psychosocial values. We used advanced behavioural data analysis of a large (total N = 539) sample of women from across the eating restraint spectrum, including those with anorexia nervosa (n = 31), recovered from anorexia nervosa (n = 23), and subclinical women with varying levels of eating restraint (n = 485), obtained from an online experiment, public event and laboratory-based study. We found that social, motivational values regarding body appearance have a significant effect on value-based, decision making in eating restriction. Subsequently, validated descriptive and predictive advanced computational modelling indicated that these behaviours are driven by an aversion to risk rather than loss, with desirable body outcomes being associated with less risk aversion, and undesirable body outcomes linked to greater risk aversion. These findings indicate that cognitive and social factors influence eating decisions by distinct mechanisms.